CMM‐based method for assessing the volume change of retrieved polyethylene cups in MoP total hip replacements. Issue 2 (19th April 2020) - Hua, Xijin; Li, Junyan
Abstract : Wear occurring at the bearing surface and the consequent generation of wear debris has been identified as the primary cause of aseptic loosening in metal‐on‐polyethylene (MoP) hip joint replacements. The accurate estimation of volume change in polyethylene cups due to creep and wear is, therefore, an important step for identifying the cause of failure and improving the longevity of MoP prosthesis. The purposes of this study were to present and apply a co‐ordinate measuring machine (CMM)‐based method for assessing the volume change of retrieved components due to wear and creep by using a combination of CMM data and a bespoke computer programme. The method was firstly validated against the standard gravimetric technique, and then applied to four retrieved polyethylene cups for wear assessment and analysis. The results show that the volume changes calculated using the present method match well with those assessed through the gravimetric technique. The CMM‐based method presented in the study is capable of effectively and reliably determining the volume change and characterising the wear patch of retrieved components from MoP hip joint replacements.